Relationship between Grades of Bladder Cancer with the Level of Arsenic in Drinking Water (Bangladesh Journal of Urology, 2022)
Background: Arsenic is a heavy metal and it is considered carcinogenic to humans. In Bangladesh, most of the people consume arsenic polluted water above the nationally accepted level. Several studies have demonstrated that the ingestion of arsenic in drinking water is a strong risk factor for several malignancies including urothelial carcinoma. Clinicopathological features of bladder cancer are related to the amount of arsenic exposure and duration of arsenic exposure into the urinary tract and other risk factors. Aim of the study was to see the relationship between grades of bladder cancers with the level of arsenic in drinking water.Objective: To see the relationship between the grades of bladder cancer with the level of arsenic in drinking water.Materials and Methods: This was a retrospective cross-sectional study done in the department of urology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka. In this study, a total of 72 histopathologically proven urothelial bladder carcinoma and history of at least 10 year underground water consumption patients were enrolled. Among them 12 patients were excluded from the study because no arsenic was found in sample underground drinking water. So, 60 patient was participants for this study. Sample of participant’s drinking water was collected by a selective non-reactive container. The level of arsenic level in microgram/Liter was measured by standard kit method and the level of arsenic was recorded.Results: Arsenic exposure 30 years or more was regardless of the amount of arsenic consumption in drinking water was found high-grade cancer. No significant statistical difference was found in the grading of carcinoma with the level of arsenic in drinking water.Conclusion: Arsenic exposure amount is not related to the grades of bladder cancer rather the duration of arsenic exposure in drinking water is related to the grades of bladder cancer.Bangladesh J. Urol. 2021; 24(2): 141-145